Overview of the Philosophy of Science on the Nature of Interdisciplinary Islamic Studies - Kaharudin, Rizal Gani; Rodiah, Ita; Razimi, Mohd Shahril Bin Ahmad; Mukri, Moh. (Universitas Islam Negeri Raden Intan Lampung, 2022)
Obtaining knowledge is the right of every human being to be able to bring a better and prosperous life. Humans as Muslims seek knowledge to be an important part and Islam also does not limit useful knowledge. To stay within the corridor of religiously useful knowledge such as Islamic Studies also requires a broad perspective through cross-study reviews. Construction of Islamic Studies can discuss many issues of life in terms of other scientific studies that support or can be referred to as Interdisciplinary Islamic Studies. This article is intended to find out the nature of Interdisciplinary Islamic Studies in terms of the philosophy of science. The study method used is through literature study, data collection based on literature such as books and journals. The results of the study reveal that Interdisciplinary Islamic Studies provides space for humans to overcome the complexities of existing human life problems, because these problems are not only solved based on one field of study. Interdisciplinary Islamic Studies builds a harmonious relationship between Islamic Studies and Science. The relationship between the two needs to be done to contribute to the good of both of them, so that this study can produce comprehensive and moral knowledge.